The virus and the economy - Brian Martin (Social Medicine Publication Group, 2020)
What is the best way to respond to covid-19? There is commonly assumed to be a trade-off between lives and the economy: precautions and controls are needed to save lives but they cause damage to the economy. There's an unstated assumption in this thinking, namely that "the economy" is vital to people's wellbeing. This needs to be questioned. It has been long known that the Gross Domestic Product or GDP is not an accurate reflection of people's wellbeing. GDP is boosted by negatives such as traffic accidents, environmental destruction and ill health. A deeper problem is that people's happiness levels are not very sensitive to increases in average income, at least above some basic level. Happiness depends more strongly on things like close personal relationships, having a purpose in life, physical activity, expressing gratitude and helping others. In countries with a high GDP per capita, average happiness levels have been mostly stable for decades despite continuing economic growth.